Building and construction students’ skills development for employability–reframing assessment for learning in discipline-specific contexts - Ruge, Gesa; McCormack, C. (2017)
The international debate on student skills development for employability has advanced institutional initiatives for teaching and learning, but to date lacks detailed research studies mapping disciplinary implementation linked to student learning feedback. This paper reports on a five year higher education research study from Australia framed by a reflective practice-based methodology. Students in the undergraduate discipline of building and construction management monitored the development of their academic attributes and skills for employability. This work contributes new knowledge on constructive alignment and implementation of assessment for learning and early professional skills development. Research findings indicate that student skills for employability are facilitated through: (1) Discipline-based curriculum design linking university and industry skills expectations. (2) Clear interweaving of learning contexts and assessments for students to experience and identify academic and professional learning dimensions (metacognition). (3) Constructive alignment for skills development through scaffolded assessment learning. (4) A ‘constructive, explicit and reflective’ teaching approach engaging students in their own generic and professional skills development.